Development of Learning Media for Learning Beginning Reading Based on Augmented Reality for Autistic Children - Lailatul Fitria (Department of Special Education, 2020)
This research is motivated by the characteristics of autistic children who are very complex. Autistic children have two main characteristics, namely obstacles in social communication and behavior (DSM V). Inside this is in accordance with the ability of children with autism which then becomes an advantage to be given in visual form (sensory process). Visual ability is a major factor in making the beginning of Augmented Reality-based reading learning media design for autistic children. This type of research is R&D research development. The research step adopts the Thiagrajan 4D theory (Determine, Design, Development and Dissemination) with implementation up to the development step. The object of this research is the early class autism class at the Inclusion school, namely UPT Lemah Putro 1 SD and Muhammadiyah 2 Tulangan Elementary School. Trials on respondents were conducted on specialists in the field of special needs, class and accompanying teachers. Based on the results of the validation and the results of the questionnaire respondents stated that the media for learning to read in the beginning based on augmented reality for autistic children can be applied with the approval of the average validity of 4.71 and the average results of trials on respondents 99.46%.